Kadar Hemoglobin, Depresi, dan Nyeri Memperberat Kelelahan pada Anak yang Menjalani Kemoterapi - Agnita Utami; Siti Chodidjah; Fajar Tri Waluyanti (STIKes Hang Tuah Pekanbaru, 2020)
Chemotherapy is a cancer treatment that is most widely used in children and can lead to fatigue. The prolonged and improperly treated fatigue can lead to decreased quality of life of the children. The objective of this study is to analyze factors associated with fatigue in children undergoing chemotherapy. The study design is cross-sectional. The sample in this study are 101 children aged 8-18 years who were undergoing chemotherapy in three public hospital in Jakarta. Sampling techniques were used consecutive sampling. The study shown significant relationships among levels of hemoglobin (p= 0,021), pain (p= < 0,001), sleep quality (p=0,046), and depression (p= <0,001) with fatigue in children undergoing chemotherapy. The multivariate analysis shows that there are three factors that most contribute to fatigue that are hemoglobin levels, pain, and depression. Nurse need to conduct an assessment of the factors that most contribute to fatigue so that it can perform appropriate nursing interventions to reduce fatigue in children Keywords: Chemotherapy, Children, Fatigue,